2021
DOI: 10.1186/s12974-021-02341-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying antidepressant effect of transcutaneous auricular vagus nerve stimulation on CUMS model rats based on hippocampal α7nAchR/NF-κB signal pathway

Abstract: Background Stress-induced neuroinflammation was considered to play a critical role in the pathogenesis of depression. Transcutaneous auricular vagus nerve stimulation (taVNS) is a relatively non-invasive alternative treatment for patients suffering from major depressive disorder. The anti-inflammatory signal of vagus nerve is mediated by α7 nicotinic acetylcholine receptor (α7nAchR), and the hippocampus, the region with the most distribution of α7nAchR, regulates emotions. Here, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 63 publications
(66 reference statements)
2
35
0
Order By: Relevance
“…α- and β-adrenergic receptor activators indirectly activate NF-kB [ 143 ], and α-adrenergic receptor blockers reduce stress-induced IL-6 elevation in peripheral blood in humans [ 144 ]. Parasympathetic excitation and acetylcholine release activate the A7 subunit of the nicotinic acetylcholine receptor (NAChR), which regulates the transcription and translation of cytokines and exerts anti-inflammatory effects [ 145 147 ]. Studies have shown a 42–53.1% two-year remission rate for refractory depression with VNS (≥50% reduction in HDRS scores from baseline) [ 148 , 149 ].…”
Section: Neuromodulation Therapy Reduces Cytokines Production and Imp...mentioning
confidence: 99%
“…α- and β-adrenergic receptor activators indirectly activate NF-kB [ 143 ], and α-adrenergic receptor blockers reduce stress-induced IL-6 elevation in peripheral blood in humans [ 144 ]. Parasympathetic excitation and acetylcholine release activate the A7 subunit of the nicotinic acetylcholine receptor (NAChR), which regulates the transcription and translation of cytokines and exerts anti-inflammatory effects [ 145 147 ]. Studies have shown a 42–53.1% two-year remission rate for refractory depression with VNS (≥50% reduction in HDRS scores from baseline) [ 148 , 149 ].…”
Section: Neuromodulation Therapy Reduces Cytokines Production and Imp...mentioning
confidence: 99%
“…4). The amphetamine (AMP) model [25, 26] was established by intraperitoneal injection of 2.5 mg/kg amphetamine for 10 days. For the corticosterone (COR) model 20 mg/kg corticosterone was intraperitoneally injected for 28 days [15, 27].…”
Section: Resultsmentioning
confidence: 99%
“…In that investigation, stimulation from the ear vagus branch traveled via the vagus nerve to the medulla oblongata, establishing an ear–brainstem connection. Several other studies using electric stimulation or TMS to stimulate the vagus have suggested that vagus fibers are distributed in the ear ( Fang et al, 2016 ; Zhang Y. et al, 2019 ; Luo et al, 2020 ; Wang et al, 2021 ; Zhang et al, 2021 ). Auricular acupuncture may influence the central nervous system through sensory circuitry, enhancing the excitability of the motor cortex through the sensory cortex.…”
Section: Discussionmentioning
confidence: 99%